The Politics of Fossil Fuel Subsidies and their Reform - Skovgaard, Jakob; van Asselt, Harro (Physical Sciences, 2018)
This comprehensive volume focuses on the politics of fossil fuel subsidies and provides insights from numerous case studies, applying a variety of political and economic theoretical approaches. Ideal for researchers, practitioners, and students of political science, international relations, and public policy. This title is also available as Open Access.